Pengaruh Strategi Joyfull Learning terhadap Minat Belajar Siswa pada Mata Pelajaran PAI di SMP N 1 Sungai Pua Kabupaten Agam - Nurjannah, Nurjannah; Arsya, Fajriyani (YASIN, 2024)
This research aims to determine the magnitude of the influence of the joyful learning strategy on the personal learning interest of class VII students in PAI learning. This research uses a quasi-experimental research method by taking two classes which are used as an experimental class and a control class. This research is a quantitative experimental research, by giving a pre-test and post-test to 52 students in both classes. The sampling technique used for data collection was a learning interest questionnaire. The data analysis technique uses normality, homogeneity tests, then continues with hypothesis testing. The results of the analysis and discussion of the research data obtained a sig. (2-tailed) value for the overall joyfull learning strategy and interest in learning, which shows that there is a significant relationship between the joyfull learning strategy and students' interest in learning in Islamic Religious Education subjects at SMP N 1 Sungai. Pua Agam Regency for the 2023/2024 academic year. The results of the research show that the results of the hypothesis testing that was carried out in the experimental class and control class obtained a sig value. (2-tailed) = 0.010 < α = 0.05, which means H0 is rejected and Ha is accepted. Based on the results of these calculations, it can be concluded that there is an influence of the joyful learning strategy on students' interest in learning in class VII PAI subjects at SMP N 1 Sungai Pua, Agam Regency.